An Examination of "On-The-Job" Writing of Recent College of Agricultural Sciences Graduates - Dennis C. Scanlon; Catherine A. Baxter (Journal of Applied Communications, 1993)
This study was designed to describe the amount and kind of writing recent College of Agricultural Sciences baccalaureate degree graduates complete on-the job, their perceptions of the importance of on-the-job writing, and the graduates' level of satisfaction with their writing preparation at Penn State.